Hubungan Dukungan Suami, Paritas dan Pekerjaan Dengan Kejadian Postpartum Blues di Wilayah Kerja Puskesmas Krueng Barona Jaya Tahun 2025 - Rona Devi; Khaira Rizki; Nurul Sakdah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The phenomenon among pregnant women at the Krueng Barona Jaya Community Health Center, Aceh Besar Regency, showed that mothers with adequate husband’s support were less likely to experience postpartum blues. In contrast, limited husband’s support, parity, and employment were considered contributing factors. This study aimed to determine the relationship between husband’s support, parity, and employment with the incidence of postpartum blues in the Krueng Barona Jaya Community Health Center working area in 2025. A quantitative cross-sectional design was used. The study was conducted from June 23 to July 10, 2025, involving 266 pregnant women, with 73 respondents selected through proportional random sampling. Data were analyzed using univariate and bivariate analyses with SPSS version 26. Chi-square analysis showed a significant relationship between husband’s support and postpartum blues (p = 0.01 < 0.05) and between parity and postpartum blues (p = 0.02 < 0.05). Employment was not significantly associated with postpartum blues (p = 0.32 > 0.05). The study concluded that husband’s support and parity were associated with postpartum blues, whereas employment was not associated with postpartum blues among mothers in the Krueng Barona Jaya Community Health Center working area, Aceh Besar.